Integrating industrial tourism in active industrial companies: Advantages, strategies, and barriers: A Delphi methodology approach - Montenegro, Z.; Marques, J.; Sousa, C. (Proceedings of the International Workshop “Tourism and Hospitality Management” (IWTHM2023), 2023)
Purpose: This article is part of a broader ongoing research project, which aims to find scientifically relevant information on how to incorporate industrial tourism into active industrial businesses whose primary focus is industrial production rather than tourism. Its methodological basis is the Delphi methodology, with the participation of 27 experts from various fields. After applying a first round of questionnaires, it was possible to identify advantages, disadvantages, strategies, and barriers to implementing Industrial Tourism in industrial companies. There is a growing interest in Industrial Tourism in Portugal; however, its applicability in industrial companies still needs to be studied. Being Industrial Tourism, one of the promoters of regional development, is it also important for the strategies of industrial companies in activity? What are the critical points of this relationship? This work also intends to contribute to the identification of the impacts of this product in industrial companies, as well as strategies and barriers to its implementation.